2018
DOI: 10.3892/ol.2018.9735
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation: A key process in skin tumorigenesis (Review)

Abstract: The extremely delicate shift from an inflammatory process to tumorigenesis is a field of major scientific interest. While the inflammation induced by environmental agents has well known underlying mechanisms, less is known concerning the oncogenic changes that follow an inflammatory chronic status in the tissue microenvironment that can lead to pro-tumorigenic processes. Regardless of the origin of the environmental factors, the maintenance of an inflammatory microenvironment is a clear condition that favors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 163 publications
1
101
0
Order By: Relevance
“…Thus, TLR-4 expression is higher in actinic keratoses compared to normal skin and in cSCC compared to actinic keratoses. It has been shown that the inhibition of their function reduces the harmful effects of UV on the keratinocytes [5].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, TLR-4 expression is higher in actinic keratoses compared to normal skin and in cSCC compared to actinic keratoses. It has been shown that the inhibition of their function reduces the harmful effects of UV on the keratinocytes [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, as ulceration and typical pyogranulomatous inflammation was prominent in majority of histological sections with reported clinical signs of inflammation, the greatest possibility seems to be due to self-trauma. However, as inflammation could promote tumorigenesis and tumor progression (Hensler and Mueller, 2013;Neagu et al, 2019), it might suggest the correlation between skin tumorigenesis and inflammation in canine species, as other kinds of cancer in dogs (Morrison, 2011). In addition, this study provides evidence that a rapid or progressive increase in mass size or multiple nodules throughout the body can be indirect indicators for tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cells can induce and help maintain tumor angiogenesis by releasing inflammatory factors, stimulating tumor cell proliferation and thus supporting their metastasis and spread and promoting tumor tissue infiltration. Inflammatory biomarkers were found to be associated with the prognosis of patients with melanoma (31)(32)(33)(34). FNAC is mainly used as a diagnostic tool and cannot completely remove tumors.…”
Section: Discussionmentioning
confidence: 99%